2006
DOI: 10.1007/s00395-006-0603-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Systolic torsion in dilated cardiomyopathy: Reversal of apical rotation at mid-systole characterized with magnetic resonance tagging method

Abstract: Left ventricular (LV) torsion plays an important role in squeezing the blood out of the heart. To characterize the systolic torsion in LV dysfunction, we studied using magnetic resonance imaging myocardial tagging method in 26 subjects: 17 patients with dilated cardiomyopathy (DCM, LV ejection fraction [EF], 27 +/- 8%) and 9 healthy control subjects. Grid-tagged LV short-axis cine images were acquired at base, mid and apex levels. Tag-intersections were tracked during the systole, thereby determining rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 28 publications
11
56
0
1
Order By: Relevance
“…78 The impact of prolonged systolic forces during ejection was observed by Stuber et al, 74 employing tagging MRI studies in patients with aortic stenosis (Figure 12) and also in patients with dilated cardiomyopathy. 79 Systolic contraction extended into the isovolumic phase (previously termed early diastole), and a similar pattern was observed after transient ischemia 78 to produce diastolic dysfunction (Figures Xa, Xb, Xc, and XI in the online-only Data Supplement). Sonomicrometer crystal studies demonstrated that extended descending segment contraction limits the normal hiatus (Ϸ80 ms interval) between cessation of descending and ascending segment shortening to generate an abnormal pattern that is remedied by sodium-hydrogen exchange inhibitors.…”
Section: Discussionmentioning
confidence: 63%
“…78 The impact of prolonged systolic forces during ejection was observed by Stuber et al, 74 employing tagging MRI studies in patients with aortic stenosis (Figure 12) and also in patients with dilated cardiomyopathy. 79 Systolic contraction extended into the isovolumic phase (previously termed early diastole), and a similar pattern was observed after transient ischemia 78 to produce diastolic dysfunction (Figures Xa, Xb, Xc, and XI in the online-only Data Supplement). Sonomicrometer crystal studies demonstrated that extended descending segment contraction limits the normal hiatus (Ϸ80 ms interval) between cessation of descending and ascending segment shortening to generate an abnormal pattern that is remedied by sodium-hydrogen exchange inhibitors.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to the balance of endocardial and epicardial forces, rotation patterns are influenced by the electric activation sequence, with an earlier electrical depolarization of the subendocardial fibers (33). LV geometry also likely plays a role in LV twist through relative change in LV fiber orientation secondary to LV remodelling as has been shown in adults with myocardial disease (8,18). Given the observations of the current study, we postulate that the differences in LV twist mechanics between NPs and YPs would suggest fundamental differences in LV myocardial architecture, which may contribute to the enhanced response of the NP LV to tachycardia.…”
Section: Discussionmentioning
confidence: 98%
“…Peak rotation at the apex may range from 5.7º to 11.2º. Maximum systolic torsion in normal hearts has then been found to range from 6.1º to 14.5º (Helle-Valle et al 2005;Kanzaki et al 2006;Nakai et al 2006;Takeuchi et al 2006). An example of the rotational motion of a normal, healthy heart is presented in Figure 5 below.…”
Section: Rotational Motionmentioning
confidence: 98%
“…Using the same short axis images, rotational motion around a central point in the LV can be measured with STE. Both radial and rotational motion measurements, derived from STE, have recently been used in a variety of settings to assess cardiac function (Borg et al 2008;Chung et al 2006;Delhaas et al 2004;Dohi et al 2008;Kanzaki et al 2006;Suffoletto et al 2006;Tops et al 2007). …”
Section: Speckle Tracking Echocardiographymentioning
confidence: 99%